(untitled) (Polish Yearbook of International Law, 2023)
This contribution discusses the unresolved claims of Poland and Germany arising from the destruction, removal, and appropriation of cultural property during and immediately following the Second World War; viewed against the background of the 50th anniversary of the 1970 Warsaw Treaty and the 30th anniversary of the 1990 2+4 Treaty. It provides an analysis of the extent to which these and other bilateral treaties between Germany and Poland impose legal obligations to restore or compensate for the destruction or loss of cultural property. Finally, it suggests pragmatic solutions to overcome the convoluted political, diplomatic and legal debates in the spirit of “cultural internationalism” and in line with the proposals of the Copernicus Group of Polish and German historians.